Industrial Frying Process - J. B. Rosseli (Grasas y Aceites)
This paper is concerned with the industrial frying process and in particular the role of the frying oil and the influence this has on the food. Attention is drawn to various factors that can adversely affect the quality of the frying oil. In this paper the term «frying oil» is used. Other publications may refere to frying fat or frying shortening. As these are all used well above their melting points, and are fully liquid, the term oil is preferred by the present author, there being no quality difference between the products so named. The quality of oil or fat used for frying is of paramount importance with regard to the quality of the fried food. The amount of oil absorbed in different fried foods varies; battered fish or chicken absorb about 15% frying oil, while breaded fish or chicken absorb up to 20% frying oil. The amount of oil absorbed by doughnuts varies from 15-20% of their final weight. This is, of course, in addition to the shortening used in preparation of the dough, giving a final oil/fat content of up to 30%. Standard or traditional potato crisps absorb the highest quantity of oil, and up to 35 or 40% of the final food may be frying oil. Recently, modern technology has been introduced to produce low-fat crisps, but these still have about 20% absorbed oil. It should therefore be remembered that the fat used for frying becomes part of the food we eat. The most important aspect of industrial frying is therefore the frying oil, and in surveying factors that affect frying oil quality, this paper reviews (a) oil properties and composition; b) transport, packaging and storage of oil; c) the nature of the food fried and its interaction with the frying oil; d) the frying equipment and the process of frying; and e) the evaluation of the quality of the frying oil during use. Each of these factors is important in its own way, and it is of no advantage to concentrate on one or two, or even three, of these aspects without appreciating that there may be additional influences on the quality of the frying oil, and thus the fried food.